Winding type secondary battery cell
By setting a polymer electrolyte coating with a specific composition at the corner of the negative electrode sheet of the winding secondary battery cell, the lithium evolution problems caused by poor wetting of the electrolyte and bending extrusion are solved, and the electrochemical performance and safety performance are improved.
Patent Information
- Application Number
- CN202411892743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The existing winding secondary battery cells have poor electrolyte wetting at the corners of the negative electrode sheet, low ion transmission efficiency, and due to bending and extrusion, the active material layer of the negative electrode sheet is easily damaged, resulting in lithium corner analysis problems, affecting electrochemical performance and safety.
A polymer electrolyte coating of a specific composition is provided at the corner of the negative electrode sheet. The coating includes organic polymer and inorganic particles, with a mass ratio of (0.5-10): 1. The thickness of the coating is determined by calculation to provide effective protection and electrolyte wetting at the corners.
Effectively alleviate the bending and extrusion effect of the negative electrode sheet at the corners, improve the wettability of the electrolyte, improve the electrochemical performance and safety performance, and avoid lithium evolution problems.
Smart Images

Figure BDA0005201023210000121 
Figure BDA0005201023210000131 
Figure HDA0005201023240000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a wound secondary battery cell. Background Art
[0002] A major defect of the existing wound secondary battery is that the corner area of the negative electrode sheet after winding not only has poor electrolyte wettability and low ion transmission efficiency, but also the active material layer on the negative electrode sheet is easily damaged and detached due to bending and extrusion, which may lead to corner lithium precipitation. The precipitated lithium dendrites will further increase the thickness of the battery cell, reduce the electrochemical performance, and even puncture the diaphragm to cause a short circuit. For this reason, people have tried to make several improvements to the secondary battery cell: (1) thickening the active material layer of the negative electrode sheet, but this approach will significantly reduce the energy density and heat dissipation performance of the secondary battery cell; (2) setting a ceramic coating at the corner of the negative electrode sheet or directly removing the active material on the positive electrode sheet at the corner to reduce the lithium ion shuttle effect of the positive electrode sheet, thereby alleviating the lithium precipitation situation, but this will greatly reduce the energy density and capacity of the secondary battery cell; (3) additionally setting a high conductivity additive on the negative electrode active material layer at the corner to improve the ion transmission efficiency, but this approach cannot solve the bending and extrusion effect of the negative electrode sheet. Summary of the invention
[0003] The purpose of the present application is to overcome the shortcomings of the prior art and provide a wound secondary battery cell. By arranging a polymer electrolyte coating of a specific composition at the corner of the negative electrode plate, and setting the thickness of the coating according to the size of the secondary battery cell, the negative electrode plate at the corner can not only effectively alleviate the bending and squeezing effect, but also has high electrolyte wettability, and the secondary battery cell has excellent electrochemical performance.
[0004] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a wound secondary battery cell, which includes, from the inside to the outside, a plurality of layers of wound negative electrode sheets and wound positive electrode sheets, wherein a polymer electrolyte coating is provided on the negative electrode active material layer at the bending corner of the wound negative electrode sheet; the polymer electrolyte coating includes an organic polymer and inorganic particles, and the mass ratio of the organic polymer to the inorganic particles is (0.5-10):1;
[0005] The thickness of the polymer electrolyte coating on the nth layer of the wound negative electrode sheet from the inside out is d=KL 2 , L=0.5π(D0+(n-1)ΔT), K=4B / (πD0) 2, where B = 2~5; D0 (μm) is the diameter of the first layer of wound negative electrode sheet at the bending corner, ΔT = 2H1+H2+H3, where H1μm is the thickness of the diaphragm corresponding to the n-th layer of wound negative electrode sheet, H2μm is the thickness of the n-th layer of wound negative electrode sheet, and H3μm is the thickness of the wound positive electrode sheet corresponding to the n-th layer of wound negative electrode sheet.
[0006] As an embodiment of the present application, the mass ratio of the organic polymer to the inorganic particles is (0.5-5):1.
[0007] As an implementation scheme of the present application, the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the nth layer of wound negative electrode sheet from the inside to the outside is N:1, where N=Fn+G, F=0.1~0.2, and G=0.34~0.6.
[0008] As an embodiment of the present application, the organic polymer contains fluorine element.
[0009] As an embodiment of the present application, the inorganic particles include at least one of lithium lanthanum titanate, lithium lanthanum zirconate, and lithium titanium phosphate.
[0010] As an embodiment of the present application, the width of the polymer coating is (0.65-1) L μm.
[0011] As an embodiment of the present application, the d is ≤15 μm.
[0012] In a second aspect of the present application, the present application provides an electrical device, comprising the wound secondary battery cell, wherein the wound secondary battery cell serves as a power supply for the electrical device.
[0013] The beneficial effects of this application are:
[0014] The present application provides a wound secondary battery cell, which provides a polymer electrolyte coating of a specific composition at the corner of the negative electrode plate, and sets the thickness of the coating according to the size of the secondary battery cell, so that the negative electrode plate at the corner can not only effectively alleviate the bending and squeezing effect, but also has high electrolyte wettability, and the secondary battery cell has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic cross-sectional view of the bending corner of the wound secondary battery cell of the present invention.
[0016] Figure 2 It is a schematic cross-sectional view of the wound secondary battery cell of the present invention. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0018] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0019] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0020] The present application is further described below with specific embodiments:
[0021] The embodiment of the present application provides a wound secondary battery cell, which includes a plurality of layers of wound negative electrode sheets and wound positive electrode sheets from the inside to the outside, and a polymer electrolyte coating is provided on the negative electrode active material layer at the bending corner of the wound negative electrode sheet; the polymer electrolyte coating includes an organic polymer and inorganic particles, and the mass ratio of the organic polymer to the inorganic particles is (0.5-10):1;
[0022] The thickness of the polymer electrolyte coating on the nth layer of the wound negative electrode sheet from the inside out is d=KL 2 μm, L=0.5π(D0+(n-1)ΔT), K=4B / (πD0) 2 , where L=π(D0+(n-1)ΔT), K=4B / [π 2 (D0+0.5(n-1)ΔT)], where B=2~15; D0 (μm) is the diameter of the first layer of the wound negative electrode sheet at the bending corner, ΔT=2H1+H2+H3, where H1μm is the thickness of the diaphragm corresponding to the n-th layer of the wound negative electrode sheet, H2μm is the thickness of the n-th layer of the wound negative electrode sheet, and H3μm is the thickness of the wound positive electrode sheet corresponding to the n-th layer of the wound negative electrode sheet.
[0023] In some embodiments, n=2-50.
[0024] In order to solve the problems of high damage rate and low ion transmission efficiency at the corners of the negative electrode sheets of the existing wound secondary battery cells, the technical solution of the present application is to set a polymer electrolyte coating at the corners of the wound negative electrode sheets of the wound secondary battery cells. Based on the interface properties of the organic polymer, the ion transmission efficiency in the corner area can be effectively improved, and the interface resistance at the corner can be reduced. At the same time, based on the joint action and protection of the organic polymer and the inorganic particles, the stress level of the negative electrode sheets at the corners is significantly reduced, which can effectively inhibit the formation of lithium dendrites, and can also simultaneously improve the wettability of the electrolyte in this area, thereby further improving the electrochemical performance and safety performance of the wound secondary battery cells.
[0025] However, based on the winding design of the wound battery cell, the coating thickness of the polymer electrolyte at the corner needs to be set within a certain range. The technical solution of the present application is based on the Laplace law, and the winding curvature of the wound negative electrode sheet, the setting width of the coating and the thickness of the single secondary device of the corresponding winding layer are jointly constructed to specifically set the coating thickness under different numbers of layers, so as to avoid the differences in the stress surface and stress degree of the wound negative electrode sheet under different layers, which makes it difficult for the coating to exert the best protection effect.
[0026] On the other hand, in order to ensure the joint effect of organic polymers and inorganic particles, the mass ratio of organic polymers and inorganic particles also needs to be controlled within a specific range so as to achieve the best electrochemical performance of the secondary battery cell while providing mechanical protection for the electrode without affecting the electrolyte wettability and moisture retention of the negative electrode.
[0027] like Figure 1 As shown in the cross-sectional view of the corner area (non-straight area) of the wound secondary battery cell, the thickness of the polymer electrolyte coating on the nth layer of the wound negative electrode plate in the technical solution of the present application can be directly calculated by directly testing the parameters involved in the calculation method.
[0028] It should be noted that the full schematic diagram of the wound secondary battery cell is as follows Figure 2 As shown, W is a straight area, that is, a region where no coated electrode is provided, and this region can be adjusted and positioned by a winding needle when winding the secondary battery cell.
[0029] In some embodiments, the mass ratio of the organic polymer to the inorganic particles is (0.1-10):1.
[0030] Specifically, the mass ratio of the organic polymer to the inorganic particles is in the range of one or any two of 0.5:1, 1:1, 2:1, 2.5:1, 3:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 7:1, 8:1, 9:1, and 10:1.
[0031] In some embodiments, the mass ratio of the organic polymer to the inorganic particles is (0.5-5):1.
[0032] The interaction between organic polymers and inorganic particles can provide conductivity, insulation and mechanical protection for the polymer electrolyte coating, and when the ratio of the two is preferably within the above range, the coating can help the wound secondary battery cell achieve better cycle stability and electrolyte retention effect.
[0033] In some embodiments, the organic polymer contains fluorine. Specifically, the organic polymer includes polyvinylidene fluoride-hexafluoropropylene copolymer.
[0034] In some embodiments, the inorganic particles include at least one of lithium lanthanum titanate, lithium lanthanum zirconate, and lithium titanium phosphate.
[0035] In some embodiments, the average particle size of the inorganic particles is 100 to 500 nm.
[0036] In some embodiments, the components of the polymer electrolyte further include a lithium salt.
[0037] In the technical solution of the present application, an organic polymer such as polyvinylidene fluoride-hexafluoropropylene copolymer is used as a matrix, which can not only achieve good mechanical strength, thermal stability and electrochemical stability, but also achieve better interface stability. In particular, organic polymers containing fluorine elements can induce more lithium ions in the wound secondary battery cell to the interface between the negative electrode plate and the polymer electrolyte coating to form a SEI film, thereby further inhibiting the formation of lithium dendrites or "moss" structures when the battery cell is working, and improving the flexibility of the plate interface.
[0038] It should be noted that the polymer electrolyte described in the present application or the organic polymer therein can be obtained by direct purchase or prepared by a homemade method, including but not limited to mixing polymer monomers, solvents, lithium salts, inorganic particles and initiators to obtain a polymer electrolyte by in situ polymerization reaction. It can also be prepared by directly mixing a polymer electrolyte, a solvent, a lithium salt and inorganic particles, as long as it does not affect the mass ratio of the organic polymer and the inorganic particles in the obtained polymer electrolyte coating, and does not significantly affect the corresponding performance of the product.
[0039] In some embodiments, the d is ≤ 15 μm.
[0040] In some embodiments, the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the nth layer of wound negative electrode sheet from the inside to the outside = N:1, wherein N = Fn + G, F = 0.1-0.2, G = 0.34-0.6.
[0041] More preferably, F=0.16-0.18, and G=0.34-0.5.
[0042] Since the different ratios of organic polymers to inorganic particles will directly affect the degree of mechanical protection of the polymer electrolyte coating to the negative electrode and the effect of improving ion transport, the coatings with different numbers of layers need to be specifically matched. When the above-mentioned gradient ratio design is adopted, each layer of coating can exert a good gain effect on the negative electrode, and the overall electrode improvement is greater.
[0043] In some embodiments, the mass ratio of the organic polymer to the inorganic particles is confirmed by the following method: the wound secondary battery cell is disassembled, the polymer electrolyte coating is scraped off the obtained wound negative electrode sheet, and then high-temperature calcination is performed in air, and the thermal weight loss is recorded to determine the mass of the organic polymer, the residue after calcination is washed, the inorganic particles are separated, and then EDS element analysis is performed on the inorganic particles. The mass of the inorganic particles is calculated based on the metal element content in the inorganic particles, and the mass ratio of the original coating organic polymer to the inorganic particles can be calculated and determined based on the masses of the two obtained.
[0044] In some embodiments, the width of the polymer coating is (0.65-1) L μm.
[0045] Further preferably, the width of the polymer coating is (0.8-1) L μm
[0046] When confirming the thickness of the polymer electrolyte coating at the corners of each layer of the wound negative electrode sheet, L, as a key parameter, actually corresponds to the width of the corner of the negative electrode sheet, and the width of the polymer coating needs to be corrected accordingly. When the width of the coating is preferably within the above preferred range, the polymer electrolyte coating has a better effect on each layer, is better compatible with the negative electrode sheet, and the comprehensive electrochemical performance of the resulting wound secondary battery cell is better.
[0047] In some embodiments, B=3-4.
[0048] When confirming the thickness of the polymer electrolyte coating at the corners of each layer of wound negative electrode sheet, the B in the formula parameter of the K value is actually strongly correlated with the coating thickness on the bottom negative electrode sheet (at this time n-1=0, the thickness of the coating is only related to A, B and the corner diameter of the bottom negative electrode sheet). When the parameter value is within the above range, a better effect of the coating can be guaranteed.
[0049] In some embodiments, the positive electrode plate includes a current collector, a positive electrode active material layer disposed on the current collector, the positive electrode active material layer includes a positive electrode active material, and the mass content of the positive electrode active material in the positive electrode active material layer is 93-97%.
[0050] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium iron phosphate.
[0051] In some embodiments, the positive electrode material layer further includes at least one of a conductive agent and a binder.
[0052] Further preferably, the binder includes at least one of polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.
[0053] Further preferably, the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0054] In some embodiments, the thickness of the positive electrode material layer is 70 to 150 μm.
[0055] In some embodiments, the negative electrode plate includes a current collector, a negative electrode active material layer disposed on the current collector, the negative electrode active material layer includes a negative electrode active material, and the mass content of the negative electrode active material in the negative electrode active material layer is 94-98%.
[0056] In some embodiments, the negative electrode active material includes at least one of artificial graphite and silicon-doped graphite.
[0057] In some embodiments, the negative electrode active material layer further includes at least one of a conductive agent and a binder.
[0058] Further preferably, the binder includes at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.
[0059] Further preferably, the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0060] In some embodiments, the thickness of the negative electrode material layer is 50 to 150 μm.
[0061] In some embodiments, the membrane includes at least one of a polypropylene membrane, a polyethylene membrane, and a polyvinylidene fluoride membrane.
[0062] The present application also provides an electrical device, which uses the above-mentioned wound secondary battery cell as a power supply.
[0063] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:
[0064] Example 1
[0065] A wound secondary battery cell, the preparation method comprising the following steps:
[0066] Preparation of polymer electrolyte slurry: organic polymer polyvinylidene fluoride-hexafluoropropylene copolymer (Arkema 2801) and neopentyl glycol diacrylate are dispersed in a solvent of EC+DEC (volume ratio 1:1) containing 1 mol / L lithium hexafluorophosphate in a mass ratio of 1:1 and mixed evenly, inorganic particles of lithium lanthanum zirconate with an average particle size of 300 nm are added and mixed, a small amount of initiator AIBN is added and stirred evenly, and the mixture is allowed to stand to obtain a polymer electrolyte slurry;
[0067] Preparation of negative electrode sheet:
[0068] Commercially available silicon-carbon powder (containing 10 wt% silicon), conductive agent acetylene black, binder styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed in water at a mass ratio of 96:1:1.5:1.5 to prepare a slurry, which was coated on both sides of the current collector copper foil, dried, cold pressed and slit to obtain a negative electrode sheet. The thickness of the negative electrode material layer on the sheet was 64 μm. The position of the corner area during winding was determined, and a polymer electrolyte slurry of a specific thickness was cast and coated;
[0069] Preparation of positive electrode:
[0070] Commercially available lithium cobalt oxide, conductive agent carbon black, and binder polyvinylidene fluoride were mixed in NMP solvent at a mass ratio of 95:3:2 to prepare a slurry, which was coated on both sides of the current collector aluminum foil, dried, and then placed in the non-straight area of the electrode of the pre-set battery cell (i.e. Figure 1 The polymer electrolyte slurry is coated on the surface of the substrate (region), cold pressed and slit to obtain a positive electrode sheet, and the thickness of the positive electrode material layer on the sheet is 74 μm;
[0071] Preparation of electrolyte:
[0072] Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte;
[0073] Preparation of wound secondary cells:
[0074] The positive electrode sheet, the commercially available 6μm separator, and the negative electrode sheet are stacked in order and then wound. The obtained electrode assembly is placed in a packaging shell and injected with electrolyte, packaged, and formed to obtain the wound secondary battery cell, which has 20 layers of wound negative electrode sheets.
[0075] In each n-layer polymer electrolyte coating, the thickness d = KL 2 , L=0.5π(D0+(n-1)ΔT), K=4B / (πD0) 2 , where B = 1.5-3, where D0 (μm) is the diameter of the first layer of the wound negative electrode sheet at the bending corner, ΔT = 2H1+H2+H3, where H1μm is the thickness of the separator corresponding to the nth wound negative electrode sheet, H2μm is the thickness of the nth wound negative electrode sheet, and H3μm is the thickness of the wound positive electrode sheet corresponding to the nth wound negative electrode sheet;
[0076] The mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the nth layer of wound negative electrode plate is regulated by the amount of inorganic particles added, and follows the following rule: the mass ratio of organic polymer to inorganic particles = N:1, where N = 0.16n + 0.34.
[0077] The parameters of the secondary battery cell are shown in Table 1, wherein d1 is the thickness of the polymer electrolyte coating on the first layer of the wound negative electrode sheet, d20 is the thickness of the polymer electrolyte coating on the 20th layer of the wound negative electrode sheet, A is the width of the polymer coating, N1 is the mass ratio of the organic polymer to the inorganic particles of the polymer electrolyte coating on the first layer of the wound negative electrode sheet, and N20 is the mass ratio of the organic polymer to the inorganic particles of the polymer electrolyte coating on the 20th layer of the wound negative electrode sheet.
[0078] Embodiments 2 to 6
[0079] A wound secondary battery cell, which is different from Example 1 only in that the parameter values when the polymer electrolyte coating is set are different, as shown in Table 1.
[0080] Example 7
[0081] A wound secondary battery cell, the only difference from Example 3 is that the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the n-th layer of wound negative electrode plate is regulated by the addition amount of inorganic particles, and follows the following rule: the mass ratio of organic polymer to inorganic particles = N:1, where N = 0.18n + 0.45.
[0082] Example 8
[0083] A wound secondary battery cell, the only difference from Example 3 is that the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the nth layer of wound negative electrode plate is regulated by the addition amount of inorganic particles, and follows the following rule: the mass ratio of organic polymer to inorganic particles = N:1, where N = 0.1n + 0.55.
[0084] Example 9
[0085] A wound secondary battery cell, the only difference from Example 3 is that the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the n-th layer of wound negative electrode plate is regulated by the addition amount of inorganic particles, and follows the following rule: the mass ratio of organic polymer to inorganic particles = N:1, where N = 0.16n + 0.6.
[0086] Comparative Examples 1-2
[0087] A wound secondary battery cell, which is different from Example 3 only in that the parameter values when the polymer electrolyte coating is set are different, as shown in Table 1.
[0088] Comparative Example 3
[0089] A wound secondary battery cell, the only difference from Example 3 is that the thickness of the polymer electrolyte coating in the second to 20th layers is the same as the first layer of the polymer electrolyte coating.
[0090] Comparative Example 4
[0091] A wound secondary battery cell, the difference from Example 3 is that in the 20th layer of polymer coating, the thickness d=KL 2 , L=0.5πD0,K=4B / [π 2 D0], where D0 (μm) is the diameter of the first layer of the wound negative electrode sheet at the bending corner, ΔT = 2H1 + H2 + H3, where H1 μm is the thickness of the separator corresponding to the 20th wound negative electrode sheet, H2 μm is the thickness of the 20th wound negative electrode sheet, and H3 μm is the thickness of the wound positive electrode sheet corresponding to the 20th wound negative electrode sheet;
[0092] The thickness of the polymer electrolyte coating in the 1st to 19th layers is the same as that of the 20th layer of the polymer electrolyte coating.
[0093] Comparative Example 5
[0094] A wound secondary battery cell, which is different from Example 3 only in that no inorganic particles are added to the polymer electrolyte coating.
[0095] Comparative Example 6
[0096] A wound secondary battery cell, the only difference from Example 3 is that the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the n-th layer of wound negative electrode plate is regulated by the addition amount of inorganic particles, and follows the following rule: the mass ratio of organic polymer to inorganic particles = N:1, where N = 0.5n + 0.34.
[0097] Comparative Example 7
[0098] A wound secondary battery cell, the only difference from Example 3 is that the mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the n-th layer of wound negative electrode plate is regulated by the addition amount of inorganic particles, and follows the following rule: the mass ratio of organic polymer to inorganic particles = N:1, where N = 0.16n + 0.2.
[0099] Table 1
[0100] parameter <![CDATA[D0(μm)]]> A(μm) d1(μm) d20(μm) N1 N20 Example 1 6000 L 2 4.4 0.5:1 3.54:1 Example 2 6000 L 3 6.5 0.5:1 3.54:1 Example 3 6000 L 4 8.7 0.5:1 3.54:1 Example 4 6000 L 5 10.9 0.5:1 3.54:1 Example 5 6000 0.8L 4 9.8 0.5:1 3.54:1 Example 6 6000 0.65L 4 8.7 0.5:1 3.54:1 Example 7 6000 L 4 8.7 0.63:1 4.05:1 Example 8 6000 L 4 8.7 0.55:1 2.55:1 Example 9 6000 L 4 8.7 0.76:1 3.8:1 Comparative Example 1 6000 L 1 2.2 0.5:1 3.54:1 Comparative Example 2 6000 L 7 15.2 0.5:1 3.54:1 Comparative Example 3 6000 L 4 4 0.5:1 3.54:1 Comparative Example 4 6000 L 15.2 15.2 0.5:1 3.54:1 Comparative Example 5 6000 L 4 8.7 / / Comparative Example 6 6000 L 4 8.7 0.84:1 10.34:1 Comparative Example 7 6000 L 4 8.7 0.36:1 3.4:1
[0101] Effect Example 1
[0102] In order to verify the performance effect of the secondary battery cell obtained by the technical solution of the present application, the secondary battery cells prepared in each embodiment and comparative example were subjected to the following performance tests:
[0103] (1) Room temperature cycle performance test: In an environment of 25°C, the first charge and discharge were carried out. Charging: The secondary cell was charged to 4.10V at a rate of 2.5C, then charged to 4.20V at a rate of 2.5C, charged to 4.30V at a rate of 1.5C, charged to 4.53V at a rate of 1.0C, and then discharged to 3.0V at a constant current of 0.7C, for 500 cycles.
[0104] Cycle capacity retention rate = (discharge capacity of the 500th cycle / discharge capacity of the first cycle) × 100%;
[0105] The test samples were set as 5 groups of parallel samples, and the final test results were calculated as the average value of the 5 groups of parallel samples.
[0106] (2) Cyclic expansion rate test: The cyclic expansion rate test is to charge the secondary cell at a rate of 2.5C to 4.10V, then charge at a rate of 2.5C to 4.20V, charge at a rate of 1.5C to 4.30V, charge at a rate of 1.0C to 4.53V, and then discharge at a constant current of 0.7C to 3.0V for 500 cycles;
[0107] Cycle thickness expansion rate = 100% × (cell thickness after 500th cycle - original cell thickness) / original cell thickness.
[0108] (3) Rate discharge test: The secondary cell was charged to 4.53V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C, and then discharged to 3.0V at 0.2C to obtain the initial discharge capacity. The same secondary cell was then charged to 4.53V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C, and then discharged to 3.0V at 2.5C to obtain the high-rate discharge capacity.
[0109] The rate performance retention rate=100%×(initial discharge capacity−high rate discharge capacity) / initial discharge capacity.
[0110] (4) Liquid retention coefficient test: When preparing each product, weigh the mass of the secondary battery cell before injection M1, weigh the mass after injection M2, and drain the excess electrolyte after 24 hours to weigh the mass of the battery cell M3. Injection volume = M2-M1, liquid loss volume = M2-M3, liquid retention coefficient = liquid retention volume / capacity, where liquid retention volume = injection volume-liquid loss volume.
[0111] (3) Corner lithium deposition level test: Take parallel samples of the secondary battery cells obtained in each embodiment and comparative example, and perform step (1) for a cycle, then disassemble them, remove the packaging film from the secondary battery cells, unfold them along the winding direction, separate the separator and the electrode, and observe the interface of the negative electrode. If there is no lithium deposition at the corner, it is marked as level 0; if there is point-like lithium deposition at the corner, it is marked as level 1; if there is linear lithium deposition at the corner, but it is not continuous, it is marked as level 2; if there is linear lithium deposition at the corner and it is continuous, it is marked as level 3; 5 parallel samples are tested in each group, and the highest level among the samples is counted.
[0112] The test results are shown in Table 2.
[0113] Table 2
[0114]
[0115]
[0116] It can be seen from Table 2 that in the wound secondary battery cell described in the present application, the products of each embodiment can show excellent performance, the electrolyte retention coefficient of the product can reach more than 1.25, the capacity retention rate after 500 cycles at room temperature can reach more than 83.5%, the expansion rate of the battery cell after the cycle is less than 15%, and there is no lithium precipitation after the cycle. In addition, the product has excellent rate performance, the capacity retention rate in the rate test can reach more than 93%, and the comprehensive electrochemical performance is excellent. This is mainly due to the special design of the polymer electrolyte layer in the wound secondary battery cell described in the present invention. Based on the setting ratio of specific organic polymers and inorganic particles, and the functional setting of thickness, the transmission efficiency of ions in the corner area can be effectively improved, and the interface resistance at the corner can be reduced. At the same time, based on the joint action of organic polymers and inorganic particles and Protection, the stress level of the negative electrode sheet at the corner is significantly reduced, the formation of lithium dendrites can be effectively suppressed, and the wettability of the electrolyte in this area can be improved simultaneously. If the ratio of the two key substances is improperly set, or the material component is missing, as shown in Comparative Examples 5 to 7, the product will have serious lithium precipitation, the battery cell will have a high degree of expansion, and the liquid retention performance may not be guaranteed. The product cannot achieve good results under cycle or rate tests; on the other hand, the thickness of the polymer electrolyte cannot be too small, and the larger the better. Regardless of whether the thickness of each layer of coating is set according to the function described in this article, if the range is improperly set, as shown in Comparative Examples 1 to 4, the product cannot effectively suppress the stress damage of the negative electrode sheet caused by bending and extrusion and ensure the wettability of the electrolyte. The performance of the product is poor, and each product has serious lithium precipitation.
[0117] According to Examples 1 to 4, it can be seen that when B=3 to 4 in the secondary battery cell, the thickness of the polymer electrolyte coating in each layer of the negative electrode is moderate, and the overall performance is better. According to the comparison between Example 3 and Examples 5 to 6, it can be seen that in addition to the thickness, the width of the polymer electrolyte coating on the negative electrode sheet will also have a certain impact on the performance of the secondary battery cell, and the parameter L in which the width corresponds to the thickness is the most appropriate.
[0118] According to the comparison between the products of Example 3 and Examples 7 to 9, it can be seen that when the mass ratio of the organic polymer to the inorganic particles in the polymer electrolyte layer in different layers is set in a gradient manner, it can better fit the stress level at the corners of the negative electrode plates distributed at different positions in the secondary battery cell, thereby achieving better protection effect. When the mass ratio of the organic polymer to the inorganic particles in the polymer electrolyte coating satisfies N:1, where N=Fn+G, F=0.16~0.18, and G=0.34~0.5, the dimensional stability, cycle stability and rate performance of the obtained secondary battery cell are obviously better.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of this article rather than to limit the scope of protection of this article. Although the present application is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of this article can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of this article.
Claims
1. A wound secondary battery cell, characterized in that: The invention comprises a plurality of layers of wound negative electrode sheets and wound positive electrode sheets from the inside to the outside, wherein a polymer electrolyte coating is provided on the negative electrode active material layer at the bending corner of the wound negative electrode sheet; the polymer electrolyte coating comprises an organic polymer and inorganic particles, and the mass ratio of the organic polymer to the inorganic particles is (0.5-10):1; The thickness of the polymer electrolyte coating on the nth layer of the wound negative electrode sheet from the inside out is d=KL 2 , L=0.5π(D0+(n-1)ΔT), K=4B / (πD0) 2 , where B = 2~5; D0 (μm) is the diameter of the first layer of wound negative electrode sheet at the bending corner, ΔT = 2H1+H2+H3, where H1μm is the thickness of the diaphragm corresponding to the n-th layer of wound negative electrode sheet, H2μm is the thickness of the n-th layer of wound negative electrode sheet, and H3μm is the thickness of the wound positive electrode sheet corresponding to the n-th layer of wound negative electrode sheet.
2. The wound secondary battery cell according to claim 1, characterized in that: The mass ratio of the organic polymer to the inorganic particles is (0.5-5):
1.
3. The wound secondary battery cell according to claim 1, characterized in that: The mass ratio of organic polymer to inorganic particles in the polymer electrolyte coating on the nth layer of wound negative electrode sheet from the inside to the outside is N:1, wherein N=Fn+G, F=0.1-0.2, and G=0.34-0.
6.
4. The wound secondary battery cell according to claim 1, characterized in that: The organic polymer contains fluorine element.
5. The wound secondary battery cell according to claim 1, characterized in that: The inorganic particles include at least one of lithium lanthanum titanate, lithium lanthanum zirconate, and lithium titanium phosphate.
6. The wound secondary battery cell according to claim 1, characterized in that: The width of the polymer coating is (0.65-1) L μm.
7. The wound secondary battery cell according to claim 1, characterized in that: The d≤15μm.
8. An electrical device, characterized in that: The invention comprises the wound secondary battery cell according to any one of claims 1 to 7, wherein the wound secondary battery cell serves as a power supply for the electrical device.